2015
DOI: 10.1002/mma.3444
|View full text |Cite
|
Sign up to set email alerts
|

Fréchet differentiability of the elasto‐acoustic scattered field with respect to Lipschitz domains

Abstract: a Communicated by S. NicaiseWe analyse the dependence with respect to a given domain of the solution of a fluid-structure interaction scattering problem. We establish that the scattered field is continuously Fréchet differentiable with respect to the shape of the elastic scatterer. Our proof assumes that the boundary of the scatterer as well as the admissible perturbations to be only Lipschitzian. Given the applied nature of this problem and its prevalence in engineering and numerical literature, this new resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Note that most references assume at least C 2 regularity, cf. [6,2], with the exception of [5] for acoustic scattering with Lipschitz obstacles, and [14,15,16] for acoustic-elastic transmission (in fact OP ∞ ) with polygonal-shaped obstacles, and the aforementioned [11,8] for elasticity on bounded Lipschitz domain. Under Lipschitz assumption, the auxiliary problems can contain singular boundary or interface terms that do not fit in the canonical boundary Sobolev spaces, and to give sense to the problem is not trivial (cf.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that most references assume at least C 2 regularity, cf. [6,2], with the exception of [5] for acoustic scattering with Lipschitz obstacles, and [14,15,16] for acoustic-elastic transmission (in fact OP ∞ ) with polygonal-shaped obstacles, and the aforementioned [11,8] for elasticity on bounded Lipschitz domain. Under Lipschitz assumption, the auxiliary problems can contain singular boundary or interface terms that do not fit in the canonical boundary Sobolev spaces, and to give sense to the problem is not trivial (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Remark 5. Although [14,15,16] also study the auxiliary problems in PDE form, they use implicit function theorem to show differentiability, while we work directly with the solution operator and use standard analysis 4 . Other approaches to show Fréchet differentiability can be e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The case of electromagnetic scattering problems has been also studied by several authors and results can be found in [36,21,9,10,30], among other references. The case of elasto-acoustic problems was recently partially addressed in [7]. It was proved that the elasto-acoustic scattered field and its corresponding far-field pattern are continuously Fréchet differentiable with respect to the elastic domain.…”
mentioning
confidence: 99%